1999
DOI: 10.1007/s002590050365
|View full text |Cite
|
Sign up to set email alerts
|

Introducing fluorine-18 fluoromisonidazole positron emission tomography for the localisation and quantification of pig liver hypoxia

Abstract: Fluorine-18 labelled fluoromisonidazole ([18F]FMISO) has been shown to accumulate in hypoxic tissue in inverse proportion to tissue oxygenation. In order to evaluate the potential of [18F]FMISO as a possible positron emission tomography (PET) tracer for imaging of liver tissue hypoxia, we measured the [18F]FMISO uptake in 13 domestic pigs using dynamic PET scanning. Hypoxia was induced by segmental arterial hepatic occlusion. During the experimental procedure the fractional concentration of inspired oxygen (Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Bentzen et al (2002) found no correlation between [ 18 F]FMISO-PET and pO 2 electrode measurements in C3H mammary carcinomas. Piert et al (1999Piert et al ( , 2000 showed a correlation between [ 18 F]FMISO-PET data and pO 2 electrode measurements in a study of hypoxia in pig liver tissue. Until today, however, the potential of this PET technique still needs confirmation by appropriate procedures, such as comparative evaluation with nitroimidazolerelated assays.…”
Section: Discussionmentioning
confidence: 95%
“…Bentzen et al (2002) found no correlation between [ 18 F]FMISO-PET and pO 2 electrode measurements in C3H mammary carcinomas. Piert et al (1999Piert et al ( , 2000 showed a correlation between [ 18 F]FMISO-PET data and pO 2 electrode measurements in a study of hypoxia in pig liver tissue. Until today, however, the potential of this PET technique still needs confirmation by appropriate procedures, such as comparative evaluation with nitroimidazolerelated assays.…”
Section: Discussionmentioning
confidence: 95%
“…3 and 4). In the work by Piert et al (26,40), it was found that, regardless of ventilation conditions, a signicant inverse relationship existed between mean pO 2 measurements by the Eppendorf electrode and the standardized uptake value of [ 18 F ]F M ISO evaluated by PET examination in liver tissue. The authors concluded that [ 18 F ]F M ISO PET allowed for in vivo quanti cation of pig liver hypoxia.…”
Section: Hypoxia Measurements and Volumementioning
confidence: 97%
“…R aleigh et al (23) found that binding of pimonidazole in experimental mice tumours (as determined by immunohistochemistry) correlated well with pO 2 measurements, whereas this was not the case in two recent studies (24,25) using the 2-nitroimidazole EF 5 in rodent tumours and human squamous cell carcinomas, respectively. In the study by Piert et al (26) on hypoxia in the pig liver, a correlation between PET-assessed uptake of uoromisonidazole and Eppendo rf electrode measurements was shown, thus indicating that the binding of uoromisonidazole is directly related to the degree of hypoxia. In contrast, in the work by Kavanagh et al (27) no relationship was found between pO 2 measurements and the binding of misonidazole in murine tumours.…”
mentioning
confidence: 90%
“…Oxygen distributions were assessed directly by Eppendorf pO 2 measurements. They concluded that the decrease in pO 2 was associated with an increase in the FMISO standardized uptake value (SUV) under pO 2 below 20 mmHg [10,11]. Bentzen et al examined mice with mammary carcinoma using FMISO and Eppendorf pO 2 measurement.…”
Section: Introductionmentioning
confidence: 99%